Competências digitais docentes: desenvolvimento de um modelo pedagógico de autoavaliação - Siqueira, Raquel Almeida Ferreira (2024)
Training actions on the use of Digital Technologies (DT) in education and the acquisition of Digital Skills (CD) by teachers are becoming increasingly necessary for the teaching and learning process. From this perspective, the research aims to identify the profile of basic education teachers in terms of their CD, build and validate a pedagogical model for self- assessment of digital skills, called DigComp-Model, with the purpose of generating consistent data to improve public policies of teacher training. As a corollary, we define the “mixed- methodology” approach, based on the combined and sequential use of a quantitative research phase followed by a qualitative phase. As for the type, it will be exploratory-descriptive and its subjects will be Basic Education teachers enrolled in an extension course at the Federal University of Ceará. To develop this work, 4,699 people enrolled in the training course entitled Integral Learning, School Management and Educational Assessment (AIGEAE), developed between the months of February 2023 and July of the same year, participated. In conclusion, we can state that the development of digital teaching skills can also facilitate communication and collaboration with the school community in general, especially between students and different types of learning. The expected results are in line with the use of a digital platform to map CDs and propose improvements in the design of public policies for initial and continuing teacher training.